Insights into the Pathology of the α3 Na+/K+-ATPase Ion Pump in Neurological Disorders; Lessons from Animal Models - Holm, Thomas H.; Lykke-Hartmann, Karin (Frontiers in Physiology, 2016)
The transmembrane Na+-/K+ ATPase is located at the plasma membrane of all mammalian cells. The Na+-/K+ ATPase utilizes energy from ATP hydrolysis to extrude three Na+ cations and import two K+ cations into the cell. The minimum constellation for an active Na+-/K+ ATPase is one alpha (α) and one beta (β) subunit. Mammals express four α isoforms (α1-4), encoded by the ATP1A1-4 genes, respectively. The α1 isoform is ubiquitously expressed in the adult central nervous system (CNS) whereas α2 primarily is expressed in astrocytes and α3 in neurons. Na+ and K+ are the principal ions involved in action potential propagation during neuronal depolarization. The α1 and α3 Na+-/K+ ATPases are therefore prime candidates for restoring neuronal membrane potential after depolarization and for maintaining neuronal excitability. The α3 isoform has approximately 4-fold lower Na+ affinity compared to α1 and is specifically required for rapid restoration of large transient increases in [Na+]i. Conditions associated with α3 deficiency are therefore likely aggravated by suprathreshold neuronal activity. The α3 isoform been suggested to support re-uptake of neurotransmitters. These processes are required for normal brain activity, and in fact autosomal dominant de novo mutations in ATP1A3 encoding the α3 isoform has been found to cause the three neurological diseases Rapid Onset Dystonia Parkinsonism (RDP), Alternating Hemiplegia of Childhood (AHC) and Cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS). All three diseases cause acute onset of neurological symptoms, but the predominant neurological manifestations differ with particularly early onset of hemiplegic/dystonic episodes and mental decline in AHC, ataxic encephalopathy and impairment of vision and hearing in CAPOS syndrome and late onset of dystonia/parkinsonism in RDP. Several mouse models have been generated to study the in vivo consequences of Atp1a3 modulation. The different mice show varying degrees of hyperactivity, gait problems and learning disability as well as stress-induced seizures. With the advent of several Atp1a3-gene or chemically modified animal models that closely phenocopy many aspects of the human disorders, we will be able to reach a much better understanding of the etiology of RDP, AHC and CAPOS syndrome.